2005
DOI: 10.4000/assr.1112
|View full text |Cite
|
Sign up to set email alerts
|

Mise en scène de la « bonne entente » interreligieuse et reconnaissance

Abstract: Archives de sciences sociales des religions 129 | janvier -mars 2005La République ne reconnaît aucun culte Mise en scène de la « bonne entente » interreligieuse et reconnaissance Anne-Sophie LamineÉdition électronique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Whilst considered non-orthodox practice following strict interpretations of laïcité, research has shown that municipalities in France since the early 2000s increasingly facilitated and staged cooperation with religious actors (Lamine, 2005). In particular, there is a rich literature addressing the numerous joint mosque construction projects, through which local municipalities in France (and elsewhere) aimed to unify or select amongst often multiple Muslim groups in town in order ‘to construct’ one official Muslim interlocutor (Boubeker, 2006; de Galembert, 2007).…”
Section: Defining Religion ‘Worthy’ Of Placementioning
confidence: 99%
“…Whilst considered non-orthodox practice following strict interpretations of laïcité, research has shown that municipalities in France since the early 2000s increasingly facilitated and staged cooperation with religious actors (Lamine, 2005). In particular, there is a rich literature addressing the numerous joint mosque construction projects, through which local municipalities in France (and elsewhere) aimed to unify or select amongst often multiple Muslim groups in town in order ‘to construct’ one official Muslim interlocutor (Boubeker, 2006; de Galembert, 2007).…”
Section: Defining Religion ‘Worthy’ Of Placementioning
confidence: 99%
“…Writing about the Danish context, for example, Ahlin et al (2012: 411, 413) regard the proliferation of ‘inter-confessional, ecumenical, and inter-religious’ initiatives as responding to a ‘new diversity’ of ‘recent decades’. Treating ‘interfaith initiatives’ in France, Lamine (2005) identifies ‘crisis’ events such as the Gulf War (1990–1991) as instrumental in their recent proliferation, but also argues that progressive commitments to equality and increasing concerns with social cohesion likewise provoked state interest. In her overview of the Spanish context, Griera (2012: 571, 580) associates ‘the growing presence of interfaith groups, councils and initiatives all around the country’ with governmental perceptions of ‘religious diversity as a “risk factor”’ to be minimised through strategic intervention.…”
Section: The Uk Religion Policy Windowmentioning
confidence: 99%
“…The fourth set of interventions includes policy tools designed to enhance the political participation of religious organisations, such as the consultative bodies in Rennes and Toulouse and the processes of participation studied by Torrekens (2012) and Fourot (2015). Despite most European states being legally separate from religious organisations, the latter are increasingly present in governance structures (Dinham and Lowndes, 2008; Lamine, 2005) in order to inform urban policy-making.…”
Section: Conceptualising the Role Of Cities In The Governance Of Relimentioning
confidence: 99%